1962
DOI: 10.1084/jem.115.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Flora of Various Strains of Mice. Its Bearing on Their Susceptibility to Endotoxin

Abstract: Adult mice from seven different colonies were studied with regard to (a) the numbers and types of bacteria that could be cultivated from their stools; (b) their resistance to the lethal effect of endotoxins prepared from three strains of Gram-negative bacilli. See PDF for Structure In six of the seven colonies, the stools yielded large numbers of various types of lactobacilli, enterococci, and Gram-negative bacilli. Most animals in these colonies died within 48 hours following inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0
2

Year Published

1965
1965
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 11 publications
3
63
0
2
Order By: Relevance
“…It was confirmed that the indigenous lactobacilli, which could be classified into three species, colonized in different locations in the digestive tracts of rats. The intestinal microflora of rats may be influenced by various factors such as diet, environmental temperature, animal strain and stress, as several workers have observed in mice (2,6,13,15). Therefore, the experimental results cannot be generally applied to all of rats which might have different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that the indigenous lactobacilli, which could be classified into three species, colonized in different locations in the digestive tracts of rats. The intestinal microflora of rats may be influenced by various factors such as diet, environmental temperature, animal strain and stress, as several workers have observed in mice (2,6,13,15). Therefore, the experimental results cannot be generally applied to all of rats which might have different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to stressors has been shown to significantly change microbial populations in the gastrointestinal tract of both humans and laboratory animals (4,5,20,28,34,36,48). For example, the stress response to maternal separation causes a significant reduction in lactobacillus levels in young monkeys (4).…”
mentioning
confidence: 99%
“…The capability of live and heat-killed Escherichia coli cells to substitute for bacterial endotoxin in the lethal synergy involving actinomycin D has been demonstrated (11). Because Pseudomonas is a component of the normal flora of some strains of mice (12) and because of the increasing incidence of Pseudomonas infections in cancer patients (14), the capability of this bacterium to enhance the lethality of vincristine for mice was tested. Additional studies were undertaken to define the nature of the vincristine-endotoxin synergy.…”
mentioning
confidence: 99%